JURIDICAL STUDIES AGAINST DIVERSION IN CRIMINAL JUSTICE SYSTEM - Indah Setyowati; Ida Musofiana (Jurnal Pembaharuan Hukum, 2019)
The diversion provisions in the juvenile justice system law whether it has prevented children from the negative effects of the Criminal Justice System. By the way, all children who have problems with the law put the best interests of the child. The method of approach is the statutory approach and the comparative approach. Primary, secondary and tertiary legal materials obtained by the author will be analyzed using the method of systematic interpretation, namely interpretation by looking at the relationship between the rules in an interdependent law.The result, diversion is a settlement of child cases that are carried out outside formal justice with the aim of preventing children from stigmatizing children who are dealing with the law must be in accordance with the purpose of diversion in The Beijing Rules. Whereas in Indonesia, the diversion provisions in the Criminal Justice System Act of the Child are still included in the criminal justice system by giving stronger stigmatization to children who are in conflict with the law and so it is not in accordance with the purpose of diversion in The Beijing Rules. So the diversion provisions in the Child Criminal Justice System Law do not yet reflect the principle of child protection as mandated by the Child Protection Act and the Child Criminal Justice System Law. Where the diversion in the Child Criminal Justice System Law has not fully mandated the principle of the best interests of children viewed from the perspective of child protection, with a view of all issues by placing the child's position as first and foremost.